The influence of demographic variables on lecturers’ protean careers orientation - Lee, Mervyn Chia Sern; Ho, Jo Ann; Sambasivan, Murali; Wong, Foong Yee (Faculty of Economics and Management, Universiti Putra Malaysia, 2014)
The present study examined the influence of age, level of education and gender on two dimensions of the protean career orientation: values-driven attitude and self-directed behaviour. The results, based on 582 university lecturers, showed that age was a significant predictor for the values-driven attitude while educational level was a significant predictor for the self-directed attitude. Gender was significant for both values-driven attitude and self-directed attitude. For both these dimensions, female lecturers scored higher than male lecturers, indicating that women were more intent on using their own values (versus organisational values) to guide their careers (values-driven) and possessed a self-directed attitude towards career management. The results of this study provided a further understanding of the factors that influence protean careerists. Furthermore, both research and managerial implications associated with values-driven attitude and self-directed attitude were discussed.